Análise da biocompatibilidade da solução de carnoy em modelo experimental in vivo com peixe-zebra - Bastos, Elaine Cristina Bezerra (2023)
The maxillofacial complex is prone to benign lesions, including ameloblastoma and odontogenic keratocyst, which can manifest aggressively, presenting challenges in terms of recurrence. This research analyzed the biocompatibility of Carnoy’s Solution in an in vivo experimental model with zebrafish and molecular docking. An in vivo study of an experimental and longitudinal nature was conducted, using independent samples randomly divided into groups. The chosen animal model was the adult zebrafish (Danio rerio). The zebrafish were randomly selected and then transferred to a wet sponge for treatment, with oral administration (n=66) or intraperitoneal (n=66) (20 μL of the solution). The Carnoy’s solutions with chloroform (group I), Carnoy without chloroform (group II) with four levels of concentration (100%, 50%, 25%, 10%) (n=8) or controls (saline solution, n=4), then they were placed in individual cups (250 mL) containing 150 mL of aquarium water and allowed to recover, and mortality rates were assessed over 24, 48, 72, and 96 hours. Molecular docking was performed from the construction of a ferric complex and its interaction with the MDM2 receptor. The overall average survival was calculated using Kaplan-Meier curves, and the comparison between the groups was performed using the Log-Rank Mantel-Cox test (p<0.05). The Carnoy solution when used at a concentration of 100% was lethal to all animals in both groups. The same lethality rate was evidenced in the Carnoy solution with chloroform at 50%. The intraperitoneal administration route showed lower lethality rates, being evidenced by the survival of the animals for a longer period. Toxicity increased proportionally to the concentration with a statistically significant difference between the concentrations of each Carnoy without chloroform group (p=0.005) and Carnoy with chloroform (p<0.005). Overall, Carnoy with chloroform treatment appears to be more toxic than Carnoy without chloroform treatment. The ferric complex of Carnoy’s solution showed stability and a strong interaction with the MDM2 receptor. The acidity of the pH favors the bond between both. The presence of chloroform increases the toxicity of the solution and its greater interaction with the MDM2 receptor, which may justify the greater efficacy of the formulation with chloroform. Even at small concentrations, the analyzed solutions can provide a degree of toxicity, highlighting the importance of the correct disposal of these solutions in the environment